General state transitions with exact resource morphisms: a unified resource-theoretic approach. (9th October 2020) - Zhou, Wenbin; Buscemi, Francesco
Abstract: Given a non-empty closed convex subset F of density matrices, we formulate conditions that guarantee the existence of an F -morphism (namely, a completely positive trace-preserving linear map that maps F into itself) between two arbitrarily chosen density matrices. While we allow errors in the transition, the corresponding map is required to be an exact F -morphism. Our findings, though purely geometrical, are formulated in a resource-theoretic language and provide a common framework that comprises various resource theories, including the resource theories of bipartite and multipartite entanglement, coherence, athermality, and asymmetric distinguishability. We show how, when specialized to some situations of physical interest, our general results are able to unify and extend previous analyses. We also study conditions for the existence of maximally resourceful states, defined here as density matrices from which any other one can be obtained by means of a suitable F -morphism. Moreover, we quantitatively characterize the paradigmatic tasks of optimal resource dilution and distillation, as special transitions in which one of the two endpoints is maximally resourceful.